Diagnóstico molecular de PYMoV (Piper yellow mottle virus) em viveiro comercial de pimenta-do-reino - Lima, Douglas Vicente do Carmo (2021)
The black pepper (Piper nigrum) has significant economic value, being widely used in the food industry and in health because of its biochemical particularities. The infection caused by PYMoV (Piper yellow mottle virus) in crops and the aggressiveness of the symptoms have a direct influence on the losses that are potentiated when seedlings are affected. Although viruses can be asymptomatic, they can be identified mainly by the symptoms of mosaic, whitening of the veins, and fruit reduction. Methods that help in early and reliable detection can have direct benefits to growers. The objective of this work was to evaluate the occurrence of PYMoV in commercial black pepper nursery plants using the PCR technique. Plant tissues from 77 plants (symptomatic and asymptomatic) were collected from a nursery in the region of Jaguaré-ES. After extraction of total DNA, the samples were submitted to PCR reaction with specific primers to detect part of the viral genome. Only 5 plants (6.5%) tested positive for the presence of the virus, indicating a low incidence of the virus in the evaluated nursery. Among the plants analyzed there were cases in which visual symptomatology was confirmed by PCR, cases in which the negative PCR indicated that the plant was not contaminated or that the symptom observed would be indicative, for example, of a possible nutritional deficiency. We conclude that the PCR technique was efficient for the molecular identification of PYMoV in the samples evaluated. Work of this nature can bring direct benefits to producers, contributing to minimize years and losses to nurserymen and black pepper producers